2007
DOI: 10.1073/pnas.0608332104
|View full text |Cite
|
Sign up to set email alerts
|

The presenilin hypothesis of Alzheimer's disease: Evidence for a loss-of-function pathogenic mechanism

Abstract: Dominantly inherited mutations in the genes encoding presenilins (PS) and the amyloid precursor protein (APP) are the major causes of familial Alzheimer's disease (AD). The prevailing view of AD pathogenesis posits that accumulation of ␤-amyloid (A␤) peptides, particularly A␤42, is the central event triggering neurodegeneration. Emerging evidence, however, suggests that loss of essential functions of PS could better explain dementia and neurodegeneration in AD. First, conditional inactivation of PS in the adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
358
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 429 publications
(386 citation statements)
references
References 63 publications
16
358
1
2
Order By: Relevance
“…One type of specific target molecule for KChIPs is represented by the presenilins (PS1 and PS2), intracellular membrane-associated proteins (Figure 1B), mutations in which are related to early-onset familial Alzheimer’s disease [45]. The first KChIP to be identified as an interaction partner for both PS1 and PS2 was KChIP3, then dubbed “calsenilin”, because it was able to bind both calcium and presenilin [18].…”
Section: Kchips Interact With Presenilinsmentioning
confidence: 99%
See 1 more Smart Citation
“…One type of specific target molecule for KChIPs is represented by the presenilins (PS1 and PS2), intracellular membrane-associated proteins (Figure 1B), mutations in which are related to early-onset familial Alzheimer’s disease [45]. The first KChIP to be identified as an interaction partner for both PS1 and PS2 was KChIP3, then dubbed “calsenilin”, because it was able to bind both calcium and presenilin [18].…”
Section: Kchips Interact With Presenilinsmentioning
confidence: 99%
“…KChIP3 (calsenilin) and KChIP4 (CALP), both diffusely distributed in the cytoplasm when expressed alone, were shown to be targeted to intracellular membranes when co-expressed with PS2 [16,18]. Presenilins are part of a multi-protein γ-secretase enzyme complex, which mediates the γ-cleavage of amyloid precursor protein (APP) to produce Aβ peptides, a process which is dysregulated in Alzheimer’s disease [45]. Since KChIP3 (calsenilin) overexpression enhances this γ-secretase activity, it has been suspected that KChIP3 (calsenilin) represents a calcium sensor of the γ-secretase enzyme complex (Figure 1B) [46].…”
Section: Kchips Interact With Presenilinsmentioning
confidence: 99%
“…3,4 The beneficial role of Ab40 is also suggested by studies using PS1 knockout models, which undergo neurodegeneration in the absence of Ab production. 5 In the PS1 exon 10 deletion mice, there are very low levels of Ab40 but accelerated amyloid plaque deposition. 6 A very recent study shows that Ab40 inhibits Ab42-initiated amyloid deposition in vivo.…”
mentioning
confidence: 99%
“…We previously reported that conditional inactivation of PS in excitatory neurons of the cerebral cortex causes progressive memory impairment and age-related neuronal degeneration (36,37), raising the possibility that loss of PS function may underlie dementia and neurodegeneration in AD (38). Furthermore, similar inactivation of nicastrin, another key component of the ␥-secretase complex, also leads to memory impairment and neurodegeneration (39), suggesting that ␥-secretase-dependent activity of PS is important for neuronal survival.…”
mentioning
confidence: 99%